A "win-win formula:" environment and profit in circular economy narratives of value. Issue 2 (4th March 2022) - Ariztia, Tomas; Araneda, Felipe
ABSTRACT: This article describes how value is defined, mobilized, and assessed in green circular economy startups. Drawing on recent debates about value and valuation in economic life and the empirical evidence collected from 30 interviews with green entrepreneurs, we focus on unpacking the value narratives developed in circular economy business settings. More specifically, we show how value is organized around the "win-win formula" a narrative plot in which economic and environmental gains reinforce each other. We highlight several key elements that organize this win-win plot: First, business opportunity and business models work as critical discursive elements. Second, we describe how clients and investors are the main conferrers of value. Third, we show how economic survival works as the ultimate evaluative framework of a company's worth. We conclude by asserting that circular economy narratives of value are underpinned by a mostly economic mode of valuing that prevail over environmental considerations.